1969
DOI: 10.1016/0031-9384(69)90075-4
|View full text |Cite
|
Sign up to set email alerts
|

Perseveration in extinction and in discrimination reversal tasks following selective frontal ablations in Macaca mulatta

Abstract: BUTTER, C. M. Perseveration in extinction and in discrimination reversal tasks /bllowing selective frontal ablations in Macaca mulatta. PHYSIOL. BEHAV. 4 (2) 163-171, 1969.-In order to determine whether the perseverative syndrome exhibited by monkeys with frontal lobe lesions can be fractionated by partial frontal lesions, monkeys with dorsolateral frontal lesions, those with orbital frontal lesions, and those with partial orbital lesions were tested in three tasks: extinction of a food rewarded bar pressing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
236
1
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(253 citation statements)
references
References 10 publications
(12 reference statements)
13
236
1
3
Order By: Relevance
“…Interestingly, in the present study, some dissociation between acquisition and reversal stages was apparent with respect to accumbal subdivisions; while the core portion was implicated in discrimination acquisition performance, activity in the shell portion was associated with reversal learning ability. Furthermore, consistent with the role of the OFC in encoding and updating associations between stimuli and reward values (Cardinal et al, 2002;Rolls, 1996Rolls, , 2000Rolls, , 2004Tremblay and Schultz, 1999;Winstanley et al, 2004), and the lesion studies that have shown the dependence of effective reversal learning upon the integrity of this region (Butter, 1969;Dias et al, 1996aDias et al, , 1997Ferry et al, 2000;Iversen and Mishkin, 1970;Jones and Mishkin, 1972;McAlonan and Brown, 2003;Schoenbaum et al, 2002), performance of the first reversal was associated with alterations in activity in the OFC. Although further investigation is required, these results therefore appear to lie in close accordance with those of several previous studies strongly implicating orbitofrontal striatal circuitry in the processes required to update affective associations and alter behavioral output accordingly when stimulus-reward associations change.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, in the present study, some dissociation between acquisition and reversal stages was apparent with respect to accumbal subdivisions; while the core portion was implicated in discrimination acquisition performance, activity in the shell portion was associated with reversal learning ability. Furthermore, consistent with the role of the OFC in encoding and updating associations between stimuli and reward values (Cardinal et al, 2002;Rolls, 1996Rolls, , 2000Rolls, , 2004Tremblay and Schultz, 1999;Winstanley et al, 2004), and the lesion studies that have shown the dependence of effective reversal learning upon the integrity of this region (Butter, 1969;Dias et al, 1996aDias et al, , 1997Ferry et al, 2000;Iversen and Mishkin, 1970;Jones and Mishkin, 1972;McAlonan and Brown, 2003;Schoenbaum et al, 2002), performance of the first reversal was associated with alterations in activity in the OFC. Although further investigation is required, these results therefore appear to lie in close accordance with those of several previous studies strongly implicating orbitofrontal striatal circuitry in the processes required to update affective associations and alter behavioral output accordingly when stimulus-reward associations change.…”
Section: Discussionsupporting
confidence: 76%
“…While extradimensional (attentional) set shifting ability refers to the capacity to shift attentional bias between different perceptual features of complex stimuli, reversal learning relates to capacity to update associations between exteroceptive stimuli and reinforcement presentation when the contingencies between stimuli and reward presentation are reversed. These processes are also anatomically dissociable; lesions of the monkey lateral PFC (Dias et al, 1996a(Dias et al, , b, 1997 and the equivalent prelimbic and infralimbic regions of the rat medial frontal cortex (Birrell and Brown, 2000) markedly disrupt extradimensional attentional set shifting ability, while lesions of the orbitofrontal cortex (OFC) selectively impair reversal learning in both species (Butter, 1969;Dias et al, 1996aDias et al, , 1997Ferry et al, 2000;Iversen and Mishkin, 1970;Jones and Mishkin, 1972;McAlonan and Brown, 2003;Schoenbaum et al, 2002). Recently, studies have also emphasized a role for the ventral striatum in transforming reversed stimulus reward contingencies into altered behavioral responses (Cools et al, 2002(Cools et al, , 2004Crofts et al, 2001;Divac et al, 1967;Monchi et al, 2001;Rogers et al, 2000;Stern and Passingham, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in non-human primates have implicated a network of structures, including the orbitofrontal cortex, its ventral and medial striatal target zones, and the ascending monoaminergic systems, in the regulation of the ability to modify responses flexibly in reversal learning tasks (Butter, 1969;Iversen and Mishkin, 1970;Dias et al, 1996;Rolls et al, 1996;Clarke et al, 2004Clarke et al, , 2007Izquierdo et al, 2004). Butter (1969) first showed that damage to large sections of prefrontal regions could elicit perseveration in monkeys performing a discrimination reversal task.…”
Section: Neuroanatomy Of Reversal Learningmentioning
confidence: 99%
“…Butter (1969) first showed that damage to large sections of prefrontal regions could elicit perseveration in monkeys performing a discrimination reversal task. Later studies assigned difficulty with modifying behavior in response to changing reinforcement contingencies to the inferior regions of frontal lobe, namely the orbitofrontal cortex (Iversen and Mishkin, 1970;Rosenkilde, 1979;Dias et al, 1996;Rolls et al, 1996;Izquierdo et al, 2004).…”
Section: Neuroanatomy Of Reversal Learningmentioning
confidence: 99%
“…By employing a 3-choice object discrimination (see Arnsten et al 1997), we can directly examine the patterns of errors made by subjects in order to determine whether, for example, responses are perseverative or random in nature. Systematic studies in monkeys with discrete cortical lesions have demonstrated that acquisition of a novel discrimination depends largely on the infero-and mesial temporal lobe (Gaffan et al 1993), while reversal learning is additionally sensitive to orbitofrontal cortical function (Butter 1969;Gaffan et al 1993;Dias et al 1996). We hypothesized that repeated cocaine administrations would result in impaired reversal learning without affecting the acquisition of novel discriminations, behavioral effects that would indicate specific orbitofrontal cortical dysfunction.…”
mentioning
confidence: 95%